Komparasi Viabilitas Polen pada Media Brewbacker and Kwack dan Polen Germination Medium pada Berbagai Jenis Tanaman - Ningsih, Riski Meliya; Sandra, Yuke Mareta Ariesta; Badriyah, Badriyah (Jurnal Inovasi Teknologi Terapan, 2025)
Pollen is a microscopic spore that plays a crucial role in the reproduction of seed plants. Pollen management has significant benefits, especially in hybrid seed production, but its viability tends to decline during storage. This study aims to determine the best medium for pollen germination in ten different plant species, namely starfruit, pumpkin, papaya, durian, bougainvillea, four o'clock flower, sweet potato, butterfly flower, chili, and eggplant. The research method used two media: Brewbacker and Kwack (BK) and Pollen Germination Medium (PGM), with two observation times (2 hours and 4 hours). The results showed that the BK medium was suitable for sweet potato and eggplant pollen, while the PGM medium was suitable for starfruit, pumpkin, bougainvillea, and butterfly flower pollen. Meanwhile, durian and four o'clock flower pollen were able to germinate in both media. The differences in pollen germination ability were influenced by genotype, flower age, as well as temperature and humidity. This study confirms that selecting the appropriate germination medium affects pollen viability, which in turn influences the success of pollination and fruit production.